2023
DOI: 10.1038/s41598-023-33178-z
|View full text |Cite
|
Sign up to set email alerts
|

A pathogenicity locus of Streptococcus gallolyticus subspecies gallolyticus

Abstract: Streptococcus gallolyticus subspecies gallolyticus (Sgg) is known to be strongly associated with colorectal cancer (CRC). Recent functional studies further demonstrated that Sgg actively stimulates CRC cell proliferation and promotes the development of colon tumors. However, the Sgg factors important for the pro-proliferative and pro-tumor activities of Sgg remain unclear. Here, we identified a chromosomal locus in Sgg strain TX20005. Deletion of this locus significantly reduced Sgg adherence to CRC cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…adherence to colorectal cancer cells and abrogated the ability of Sgg. to stimulate cancer cell proliferation [ 22 ]. Taken together, whether Sgg.…”
Section: Discussionmentioning
confidence: 99%
“…adherence to colorectal cancer cells and abrogated the ability of Sgg. to stimulate cancer cell proliferation [ 22 ]. Taken together, whether Sgg.…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying molecular mechanisms are not known. Recently, the same group reported the identification of a 12-gene chromosomal locus named SPAR (for Sgg pathogenicity-associated region) reducing the adherence of TX20005 to the host colonic cells and abrogating its ability to stimulate cell proliferation ( 49 ). The SPAR mutant phenocopies the T7SSb knockout mutant, connecting the SPAR locus to the T7SSb.…”
Section: Discussionmentioning
confidence: 99%
“…It is uncertain whether there is a significant association between these clinical conditions, as seen in most cases of Streptococcus gallolyticus subsp. gallolyticus endocarditis, previously associated with Streptococcus bovis biotype I [ 122 , 123 , 124 , 125 , 126 ]. Stanley et al [ 127 ] found that a murine model of ischemic-reperfusion stroke showed bacteraemia caused by a specific group of commensal bacterial strains, with enterococci being the most prevalent.…”
Section: Causes Of E Faecalis Bacteraemiamentioning
confidence: 99%